RedPlane: Enabling Fault-Tolerant Stateful In-Switch Applications - Kim, Daehyeok; Nelson, Jacob; Ports, Dan R. K.; Sekar, Vyas; Seshan, Srinivasan (ACM SIGCOMM 2021, 2021)
Many recent efforts have demonstrated the performance benefits of running datacenter functions ([e.g.,] NATs, load balancers, monitoring) on programmable switches. However, a key missing piece remains: fault tolerance. This is especially critical as the network is no longer stateless and pure endpoint recovery does not suffice. In this paper, we design and implement RedPlane, a fault-tolerant state store for stateful in-switch applications. This provides in-switch applications consistent access to their state, even if the switch they run on fails or traffic is rerouted to an alternative switch. We address key challenges in devising a practical, provably correct replication protocol and implementing it in the switch data plane. Our evaluations show that RedPlane incurs negligible overhead and enables end-to-end applications to rapidly recover from switch failures.